UJI BEBERAPA KONSENTRASI EKSTRAK BIJI PINANG (Area catechu) UNTUK MENGENDALIKAN HAMA ULAT GRAYAK (Spodoptera liturra F.) PADA TANAMAN SAWI (Brassica juncea L.) - Salbiah, Desita; Laoh, Hennie; ', Eri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Mustard plants (Brassica juncea L.) is vegetable commodity that have best  prospect to be developed in  Indonesia Riau province. The armyworm is singnificant pest on mustard plants. The pesticide synthetic chemistry have many negative impacts such happened pest resistance, secondary pest explosion and environment pollution. The function of phyto pesticide such betel nuts is one of pest control way to decrease using synthetic chemistry pesticide. The purpose of this research is to exam or test ability some ectract concentration of betel nut (Areca catechu L.) armyworm (Spodoptera litura F.) pest on mustard plants. This research is done in Ethnic Implementation Unit trying field’s Agriculture Faculty of Riau University by using Completely Randomized Desingn (CRD) by 5 treatments and 4 replication.The treatments that given is some extract concentrations of betel nut (Areca catechu L.) seeds are: 0 g/l water, 10 g/l water, 20 g/l water, 30 g/l water, 40 g/l water. Extract concentration of betel nut 40 g/l able to control armyworm at mustard plants couse total mortality 83,30%.   Keywords: Mustard (Brassica juncea L.), armyworm (Spodoptera litura F.), betel nut (Areca catechu L.)